Consumers’ Awareness, Perception and Interest in Labelling of Processed Foods in Ghana: A Case of ‘Sobolo’ - Nimoh, Fred; Opoku-Agyeman, Gifty; Frimpong, Alexander Annor (Applied Studies in Agribusiness and Commerce, 2021)
Food labels contain much information that helps consumers to make decisions based on the details which are of much importance to them. The study assessed awareness, perception and factors that influence consumers’ interest in labelling of sobolo in the Kumasi Metropolis of Ashanti region, Ghana. Systematic random sampling was used to select 300 respondents from five randomly selected sub-metros and data were collected using a semi structured questionnaire. Descriptive statistics such as frequencies, tables and percentages were used to summarize the socio-economic characteristics of respondents. Perception index was used to assess the perception statements on the product labelling and the Logistic Regression Model was used to analyze the factors that significantly influence consumers’ interest in labelling of sobolo. Results of the study showed that majority (97.3%) of respondents were not aware of labelled sobolo but 67% was interested, though with low awareness. The estimated perception index (2.8) showed that consumers had positive perception about labelling of sobolo. Among the socio-economic characteristics; age, education, household income and household size and respondents’ perception on health and safety aspects of sobolo were found to significantly influence interest in labelling of sobolo. In conclusion, the study found that, consumers would prefer different information on labels and thus their interests are significantly influenced by different factors. It is recommended that efforts should be made to promote the awareness, education and interest in labelling of food products to enhance production, consumption and sustainability of the food industry.